1994
DOI: 10.1073/pnas.91.23.10997
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of AQP3, a water channel from the medullary collecting duct of rat kidney.

Abstract: The einal part of the inner medullary cleing duct exhibits a high degree ofwater permeability that is independent of increased intracellular cAMP and not accounted for by the activity of the known renal epithelial water channels CH1P28

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
0
8

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(172 citation statements)
references
References 18 publications
6
158
0
8
Order By: Relevance
“…3 and Table 2). For example, we observed the upregulation of three genes whose elevated levels may disrupt normal glucose oxidation: the plasma membrane lactate transporter MCT (monocarboxylate transporter) 2 (Slc16a7) (1) and aquaporins 3 and 7 (14,23) (Table 2). Conversely, mitochondrial NADH dehydrogenase subcomplex 5 and the mitochondrial aspartate/glutamate exchanger were progressively suppressed by PPAR␥ overexpression and/or activation ( Table 2), changes that may decrease the production of mitochondrial coupling factors.…”
Section: Discussionmentioning
confidence: 99%
“…3 and Table 2). For example, we observed the upregulation of three genes whose elevated levels may disrupt normal glucose oxidation: the plasma membrane lactate transporter MCT (monocarboxylate transporter) 2 (Slc16a7) (1) and aquaporins 3 and 7 (14,23) (Table 2). Conversely, mitochondrial NADH dehydrogenase subcomplex 5 and the mitochondrial aspartate/glutamate exchanger were progressively suppressed by PPAR␥ overexpression and/or activation ( Table 2), changes that may decrease the production of mitochondrial coupling factors.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, AQP3 cDNA was cloned from rat kidney cDNA by polymerase chain reaction (PCR); the sense strand was 5'-CGGGATCCCATGGGTCGACAGAAGGAGTT-3', and the antisense strand was 5'-GCTCTAGAGGGTTTTATGGGGT-GTCC-3' (underlined sequences indicate inserted BamHI and XbaI sites, respectively). These primers were derived from the rat AQP3 sequence [10] (GenBank TM accession No. L35108).…”
Section: Preparation Of Aqp3 Crnamentioning
confidence: 99%
“…Although several studies reported that AQPs may increase membrane permeability to glycerol (Stroud et al, 2003), urea (Echevarria et al, 1994), and perhaps CO 2 (Uehlein et al, 2003) or even ions (Yasui et al, 1999;Hazama et al, 2002), it is now well established that most of these transmembrane proteins increase the water permeability of cellular membranes. Thus, AQPs are potentially playing a role in many physiological processes (Maurel et al, 2002;Tyerman et al, 2002;Luu and Maurel, 2005) involving water flow through membranes.…”
mentioning
confidence: 99%